2013
DOI: 10.1016/j.cmet.2013.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Human but Not Mouse Adipogenesis Is Critically Dependent on LMO3

Abstract: SummaryIncreased visceral fat is associated with a high risk of diabetes and metabolic syndrome and is in part caused by excessive glucocorticoids (GCs). However, the molecular mechanisms remain undefined. We now identify the GC-dependent gene LIM domain only 3 (LMO3) as being selectively upregulated in a depot-specific manner in human obese visceral adipose tissue, localizing primarily in the adipocyte fraction. Visceral LMO3 levels were tightly correlated with expression of 11β-hydroxysteroid dehydrogenase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 48 publications
(24 reference statements)
5
61
0
Order By: Relevance
“…1). The gene expression changes were consistent with previously published data confi rming that SGBS preadipocyte differentiation is a reproducible model for the study of human adipogenesis ( 12,(37)(38)(39)(40).…”
Section: Lipid-quant Data Analysis and Outputsupporting
confidence: 80%
“…1). The gene expression changes were consistent with previously published data confi rming that SGBS preadipocyte differentiation is a reproducible model for the study of human adipogenesis ( 12,(37)(38)(39)(40).…”
Section: Lipid-quant Data Analysis and Outputsupporting
confidence: 80%
“…LMO3 has been recently demonstrated to be upregulated by GCs, to correlate with 11BHSD1 levels and to promote adipogenesis via increasing PPARg tone in human VAT (90). As LMO3 is not expressed in rodent visceral tissue, this mechanism could also explain the well-known striking difference in GC-induced visceral adiposity in humans and mice.…”
Section: European Journal Of Endocrinologymentioning
confidence: 85%
“…Very recently, Lindroos et al (24) reported that the adaptor protein LMO3 is induced by glucocorticoids and modulates adipogenesis in human but not mouse tissues. Whether LMO3 and Dexras1 interface in regulating adipogenesis is unclear.…”
Section: Discussionmentioning
confidence: 99%